Адам и Ева как прообраз Нового Адама и Новой Евы (по учению святителя Иринея Лионского, Тертуллиана и святителя Викторина Петавийского). К вопросу о теории рекапитуляции в раннехристианском богословии - Nikolay A. Khandoga (Warszawskie Studia Teologiczne)
The doctrine of Adam and Eve as prototypes of New Adam and New Eve (the so-called theory of recapitulation) was first encountered in the epistles of the apostle Paul. Revealing the main feature of this teaching, the supreme apostle reports that the disobedience and sin that Adam and Eve committed were corrected by New Adam and New Eve (see: Rom. 5, 14-15). As a result, instead of the death of Adam and Eve and their descendants (by bodily birth), humanity received immortality, starting with New Adam and New Eve and their descendants (by spiritual birth). Subsequently, the pre-nicene christian writers, for example, Irenaeus of Lyon, Tertullian and Victorinus of Poetovio, resorted to the doctrine of Adam and Eve as prototypes of New Adam and New Eve.